2022
DOI: 10.1371/journal.pone.0273187
|View full text |Cite
|
Sign up to set email alerts
|

What do university students say about online learning and the COVID-19 pandemic in central Fiji? A qualitative study

Abstract: Globally, the spread of COVID-19 has led to the closure of schools, thereby accelerating the expansion of the online learning environment. Though, Fiji National University students’ (FNU), had no option than to quickly adopt to this mode of learning, within limited period, their learning experiences are yet to be examined and documented. We used phenomenological study design to explore students’ online learning challenges, coping strategies and their perceptions on the causes of COVID-19. A total of 120 in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…This includes the inability to participate fully in online classes due to poor internet connection. The lack of a strong internet connection as one of the problems faced during online learning is consistent with the studies of other researchers (Belgica et al, 2020;Delicano, 2021;Okyere et al, 2022). This problem can have negative and lasting impacts on students' learning, particularly in subjects such as mathematics, because without a reliable internet connection, online learning would not be feasible (Belgica et al, 2020;Delicano, 2021;Kansiime & Batiibwe, 2023;Mukuka et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This includes the inability to participate fully in online classes due to poor internet connection. The lack of a strong internet connection as one of the problems faced during online learning is consistent with the studies of other researchers (Belgica et al, 2020;Delicano, 2021;Okyere et al, 2022). This problem can have negative and lasting impacts on students' learning, particularly in subjects such as mathematics, because without a reliable internet connection, online learning would not be feasible (Belgica et al, 2020;Delicano, 2021;Kansiime & Batiibwe, 2023;Mukuka et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the study of Baticulon et al (2021) revealed that household chores and other tasks make students lose focus on the teacher's discussion, especially since parents see the presence of their children at home as an opportunity to get help with the chores while other parents must work and leave their older children to care for the younger siblings while attending classes. Furthermore, similar results were found by Mamolo (2022), showing that slow and unstable internet connection and plenty of activities and chores at home were some of the main reasons students got difficulties learning the subject matter, while Okyere et al (2022) cited unstable internet service and inadequate learning environment as the challenges of online learning.…”
Section: Discussionsupporting
confidence: 72%
“…Issues such as ineffective tutorial, lack of learning devices, difficulty in accessing online platforms or poor internet connection, inappropriate learning environment, socio-cultural practices (Hu, et. al., 2022;Khanna, & Prasad, 2020;Mahyoob, 2020;Okyere et. al., 2022) and insufficient interaction between students-instructors and peers are the factors that cause students to feel loneliness, anxiety and stress in the online learning environment (Mahyoob, 2020).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…As Pokhrel and Chhetri (2022) argue "Online learning, distance, and continuing education have become a panacea for this unprecedented global pandemic, despite the challenges posed to both educators and the learners" (p.134). Some of the challenges mentioned in the study of Okyere et al (2022) included ineffective tutorial sessions, lack of learning devices, unstable internet service, inadequate learning environment, socio-cultural practices, feeling of loneliness, anxiety, and stress, and difficulties accessing online platforms and acquiring practical skills (p.21).…”
Section: Literature Reviewmentioning
confidence: 99%